2002
DOI: 10.1597/1545-1569_2002_039_0509_dmicwa_2.0.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Dental Maturity in Children with a Complete Bilateral Cleft Lip and Palate

Abstract: Objective: Dental age in children with a bilateral cleft lip and palate (BCLP) was assessed and compared with children without cleft. Design: Dental age was estimated for 74 children with a complete BCLP (54 boys and 20 girls) from 364 orthopantomograms. Nonlinear regression curves were made between 5 and 14 years of age for boys and girls separately. A comparison was made with a sample of Dutch children (91 girls and 90 boys) without oral clefts for three different age groups, namely 5, 9.5, and 14 years of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…No significant difference was found between children with complete UCLP and controls at an older age of 9 to 13 years. This finding concurred with the results of Heidbuchel et al., Poyry et al . and Prahl‐Andersen…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No significant difference was found between children with complete UCLP and controls at an older age of 9 to 13 years. This finding concurred with the results of Heidbuchel et al., Poyry et al . and Prahl‐Andersen…”
Section: Discussionsupporting
confidence: 93%
“…Many studies found that the delay in dental development begins to decrease from the age of 8 to 9.5 years—possibly due to some form of catch‐up growth . This was in contrast to the findings of Ranta, who noted that there was significantly more delay in dental development in the older age group of 9 to 12 years old (mean delay of 1.1 years) than in the younger age group of 6 to 9 years old (mean delay of 0.6 year) .…”
Section: Introductionmentioning
confidence: 78%
“…The relevant literature previously identified males as having delayed dental development. 34,35,[41][42][43] Borodkin et al reported that males were more dentally delayed than females, with an average difference of 0.96 year. 43 This could be associated with the relative delay in teeth development and emergence between boys and girls, with the former attaining their complete dentition 1 year earlier.…”
Section: Discussionmentioning
confidence: 99%
“…5,[38][39][40] Additionally, some studies showed that boys with clefts were more dentally delayed than girls. 34,[41][42][43] In assessing panoramic and hand-wrist radiographs, Al-Hadlaq et al did not demonstrate statistically significant difference among 148 Saudi male children's mean chronological, dental, and skeletal ages. 44 However, Al-Emran examined panoramic radiographs of 430 Saudi boys and girls and showed (p < 0.05) advance dental age in comparison with their chronological age.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of delayed dental maturation is in agreement with previous studies on older children with CLP. [18][19][20][21] We also found delay in mineralization of M1 inf in a previous study on infants and young children with isolated CP and UCCLP. 22,23 The delayed mineralization of the teeth observed in subjects with CP with/without a cleft lip might be related to the observed delay in somatic development (first observed as reduced body weight and later as reduced body length).…”
Section: Maturation or Mineralization Stagementioning
confidence: 52%